Policy Implementation of Non Civil Servant Educator Training in Higher Education (Study of Implementation of Rector Regulation of Malang State University Number 14 the Year 2017 Regarding Non-PNS Permanent Lecturers at State University of Malang) - Wahyu Bowo Laksono; Bambang Santoso Haryono; Mohammad Nuh (Wacana Journal of Social and Humanity Studies, 2021)
Higher education is part of the national education system that has a strategic role in educating the nation's life and advancing science and technology by paying attention to and applying human and cultural values and sustainably empowering the Indonesian people, to support Malang State University (UM) as a state university that is implementing higher education autonomy with a financial management pattern, the Public Service Agency is given the authority to appoint Non-PNS Permanent Lecturers based on the internal needs of the institution. adapted to national higher education standards. The objectives of this study are: (1) to explain the implementation of the Rector of the State University of Malang Number 14 of 2017 concerning Permanent Lecturers of Non-PNS UM (2) to determine the supporting and inhibiting factors. This study used the descriptive qualitative method. Data collection techniques used in this study were interviews, observation, and documentation. Research findings: (1) differences in the interpretation of leaders at universities and faculties and among non-PNS permanent lecturers themselves in terms of clarity of future status for non-PNS UM lecturers (2) lack of socialization related to non-PNS policies Permanent PNS UM lecturers in particular in terms of career patterns, clarification of further study S3 in the contract period (3). There are differences in policies in terms of employment status and providing incentives for education staff with the status of Non-Permanent Employees with the policy of Non-PNS Permanent Lecturers whose rights and obligations are the same as PNS.